Armed conflict and post-conflict in Colombia: inclusive education approach scope in the subject training process in demobilization and reintegration condition (2019)
The analysis on the inclusive education approachscope, is not only developed at an academic level,but also at an axiomatic one, to the extent that thisapproach represents a possibility to respond to thechallenges higher education faces, e.g., attendingspecial educational needs students in a possiblepost-conflict scenario, whilst generates an academicreflection about Johan Galtung’s Theory of Peacecontributions.